Repeatability of biometric characteristics of Juçara palm fruit (Bioscience Journal, 2016)
: Juçara is a plant that occurs in the Brazilian Atlantic Forest which presents high ecological importance to the biodiversity and is present on the list of endangered species. The fruits are known as super fruits because they present chemical characteristics of great importance. Due to its elevated economic importance and for the low number of researches with this species, the first step is to make the pre-breeding of the species. This consists in morphological characterization, which is very dependent on time and labour. Thus, the decrease of the number of evaluated measurements by individual is of great importance to the phases of pre-breeding and breeding. The objective of this work was to obtain estimates of the coefficients of repeatability and determination of six Euterpe edulis fruit characteristics to enable the prediction of the necessary number of measurements required to achieve given levels of certainty for the real values for each of the six fruit characteristics. The performances of various methods for repeatability estimation were compared. The characteristics longitudinal diameters of the fruits, longitudinal diameters of the seeds, equatorial diameters of the fruits, equatorial diameters of the seeds, fruit weights and seed weights of juçara palm fruits were measured, and the deviances, the coefficients of repeatability, the coefficients of determination, and the necessary numbers measurements for an accurate prediction of the real value of the population were estimated. The methods used do not differ as to estimate the repeatability coefficient to the longitudinal diameter characteristics of the fruit, seed equatorial diameter, fruit mass and seed mass. With 95% reliability is possible to use four (4) for mass measurements of fruit and five (5) measurements for longitudinal diameter of fruit, seed equatorial diameter, fruit mass and seed mass.